2007
DOI: 10.1542/peds.2006-1699
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome in Childhood Predicts Adult Cardiovascular Disease 25 Years Later: The Princeton Lipid Research Clinics Follow-up Study

Abstract: Evaluating children for metabolic syndrome could identify patients at increased risk of adult cardiovascular disease, making targeted interventions possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
352
0
13

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 497 publications
(394 citation statements)
references
References 24 publications
13
352
0
13
Order By: Relevance
“…In this line, changes in age-specific BMI percentile from childhood to adulthood and pediatric metabolic syndrome were found to be predictors of CVD 26 . Some studies have shown WC…”
Section: Body Composition and Single Cvd Risk Factorsmentioning
confidence: 84%
“…In this line, changes in age-specific BMI percentile from childhood to adulthood and pediatric metabolic syndrome were found to be predictors of CVD 26 . Some studies have shown WC…”
Section: Body Composition and Single Cvd Risk Factorsmentioning
confidence: 84%
“…3,4 Childhood obesity tends to track into adulthood, meaning that subjects keep their ranking position in body mass index (BMI) distribution over time. 5 Obesity in childhood is defined by BMI. However, BMI is not an appropriate measure for fat mass, which is the actual harmful factor of obesity.…”
Section: Introductionmentioning
confidence: 99%
“…* A significant difference from children with BMI percentile below than the threshold (71.3 for boys and 77.1 for girls), using x 2 test: P < 0.05. y A significant difference from children with BMI percentile below than the threshold (71.3 for boys and 77.1 for girls), using x 2 test: P < 0.01. We defined cardiovascular risk as the presence of 3 or more risk factors in children including high systolic or diastolic blood pressure, high triglycerides, low HDL-cholesterol, impaired glucose tolerance and waist circumference, following the criteria of Cook et al, which have been demonstrated to predict the risk of developing cardiovascular disease and type 2 diabetes mellitus later in adulthood in prospective studies [18,20]. The criteria utilized in the BHS and Messiah's study have not been verified to predict the development of cardiovascular disease and type 2 diabetes mellitus later in adulthood in longitudinal studies.…”
Section: Discussionmentioning
confidence: 99%
“…For lipid levels and glucose concentrations, the suggestions of Cook et al were adopted, because the criteria were used to predict adult cardiovascular disease and type 2 diabetes mellitus in prospective studies [18,20,31]. Accordingly, high TG was defined as values >1.24 mmol/L and low HDL-cholesterol was defined as values <1.03 mmol/L.…”
Section: Measurementsmentioning
confidence: 99%
See 1 more Smart Citation